Chemical Weapons in the Iran-Iraq War (1980–1988). 4. The Destruction of Iraqi Chemical Weapons - M. V. Supotnitskiy; N. I. Shilo; V. A. Kovtun (Вестник войск РХБ защиты, 2020)
After the defeat of Iraqi army in Kuwait in February 1991, on April 3, the UN Security Council (UN Security Council) adopted Resolution 687, that «decides that Iraq shall unconditionally accept the destruction, removal, or rendering harmless, under international supervision, of: (a) All chemical and biological weapons and all stocks of agents and all related subsystems and components and all research, development, support and manufacturing facilities». This UN operation was not the first forced disarmament of vanquished by victors, but it gave great impetus to the completion of the work on the Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on Their Destruction, i.e. the destruction of an entire class of weapons of mass destruction. The aim of this article was to show the process of Iraqi`s chemical weapons destruction. The destruction of Iraqi chemical weapons included the formation of legal basis (United Nations Security Council Resolution 687); the establishment of the United Nations Special Commission (UNSCOM) to inspect and oversee the destruction or elimination of Iraq’s chemical weapons directly on Iraqi territory; certain measures of political, economic (UN sanctions) and military coercion (the US and the UK military operation «Desert Fox»). In summer 1991, UNSCOM formed a Destruction Advisory Panel to develop technologies for the destruction of chemical weapons, toxic substances and their precursors. Their destruction was carried out in the period October 1992 to May 1994 on the territory of the Muthanna State Establishment. Sarin, cyclosarin, tabun and their precursors were destroyed by hydrolysis in aqueous alkaline solution using a repurposed production facility. Thus 76 tons of sarin and sarin/cyclosarin mixture, as well as 40 tons of tabun were destroyed. For the sulfur mustard, the high-temperature direct burning method was used at the special factory, established under the project of the Destruction Advisory Panel. Thus were destroyed around 400 tons of liquid sulfur mustard. Chemical munitions and containers, after the extraction of poisonous agents, were destroyed using a specially developed technique of explosive ventilation and burning. 30 chemical warheads for Al-Hussein ballistic missiles, 12,8 thousand 155-mm mustard shells, 40,5 thousand 122 mm rockets for MLRS, filled with sarin/cyclosarin, were destroyed. In general, UNSCOM managed to solve the problem of chemical disarmament of Iraq. The article describes in details the Iraq’s chemical weapons destruction technologies.